Ответ:
y+12y+36y=2cos(x)-sin(x)
49y=2cos(x)-sin(x)
y=-
y=
y= x∈R
Пошаговое объяснение:x∈R т.е. любое число
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
y+12y+36y=2cos(x)-sin(x)
49y=2cos(x)-sin(x)
y=
-![\frac{sin(x)}{49} \frac{sin(x)}{49}](https://tex.z-dn.net/?f=%5Cfrac%7Bsin%28x%29%7D%7B49%7D)
y=![\frac{2 cos(x)-sin(x)}{49} \frac{2 cos(x)-sin(x)}{49}](https://tex.z-dn.net/?f=%5Cfrac%7B2%20cos%28x%29-sin%28x%29%7D%7B49%7D)
y=
x∈R
Пошаговое объяснение:x∈R т.е. любое число